Advantages and disadvantages of sandy soils - Othman, Rashidi (Nova science publishers, inc., 2023)
This book presents the significant values of the sandy soil properties, which include biotic and abiotic components, soil protection, soil amelioration, ecological indicators, and differing from other books, forest therapy concept implementation at sandy soil heath forest areas for potential healthcare enhancement. This book may benefit people from different fields, including ecologists, landscape architects, researchers, students, etc., to understand In-depth sandy soil properties, characteristics, and functional values.